Willingness to stay or quit: evidence from migrants working in the galway bar and restaurant industry in Ireland - Olaiwola Jamiu Ogunpaimo; Kesiena Ebenade (Research in Hospitality Management)
Health and safety issues, irregular working hours and low wages frequently intensify the concerns that migrant hospitality workers experience regarding their jobs. Given these challenges, the article explores the work motivation and career intentions of migrant workers in the Galway bar and restaurant sector. The study employs the theory of work adjustment (TWA) to understand the demographics, experiences and future intentions of migrants working in Galway City’s bars and restaurants. A survey was used to collect data from 101 migrant workers. Descriptive methodology and SPSS were adopted to analyse the data collected. Research findings reveal that 53% of migrants working in Galway City’s bars and restaurants hold at least a bachelor’s degree, indicating high educational attainment in the industry. On the contrary, the majority of those willing to build a long-term career in the industry are from the EU, North America and Asia, while a more significant proportion of migrant workers from Africa and South America plan to stop working in the sector. Insights gained from the study highlight the need for targeted retention strategies to address the hospitality industry’s low employee retention issues. The implications for employee career decisions are discussed for recruitment practice and managerial applications.